PTEN inhibition preserves trigeminal nucleus caudalis neuron activation through tyrosine phosphorylation of the NR2B subunit at Tyr1472 of the NMDA receptor in a rat model of recurrent migraine. (2nd April 2016) - Qin, Guangcheng; Xie, Jingmei; Chen, Lixue; Wu, Baixue; Gui, Bei; Zhou, Jiying
Abstract : Objective: Activation of the trigeminal nucleus caudalis is believed to be involved in the pathomechanism of migraine. Evidence suggests that N -methyl-d -aspartate receptor subtype 2B tyrosine phosphorylation, originating from the trigeminal nucleus caudalis neuron dysfunction, might be a triggering mechanism for recurrent migraine. Phosphatase and tensin homolog is thought to have a neuroprotective effect in various neurologic diseases by regulating N -methyl-d -aspartate receptor subtype 2B or tyrosine phosphorylation. Thus, the aim of this study was to explore whether the recombinant adenovirus AdR-siPTEN attenuates neuron activation in the trigeminal nucleus caudalis in a rat model of recurrent migraine. Methods: Adenovirus-expressing siPTEN or RFP was independently injected into the spinal trigeminal nucleus of the rat model suffering from recurrent migraine by inflammatory soup stimulation the superior sagittal sinus of rats. Seven days later, tactile sensory testing was performed to detect the tactile threshold. Immunofluorescence, Immunohistochemistry, and western blot assay were done to measure PTEN, NR2B, NR2B-pTyr1472, and c - Fos levels in the trigeminal nucleus caudalis of recurrent migraine rats. Results: A significant increase ( p  < 0.05) in neuron c - Fos content, an indicator of neuron activation, was detected in the trigeminal nucleus caudalis in a rat model of recurrent migraine. However, neuron activation in the trigeminal nucleus caudalis was attenuated by pretreatment with AdR-siPTEN. Moreover, the attenuated effect was potentially mediated by tyrosine phosphorylation of the NR2B-p1472 tyrosine site in the trigeminal nucleus caudalis, as seen in rat brain slices. Conclusion: These results suggest that, phosphatase and tensin homolog might be a novel and promising candidate for future treatment or prophylaxis of recurrent migraine by attenuating neuron activation in the trigeminal nucleus caudalis.